Molecular basis of calcium-sensitizing and desensitizing mutations of the human cardiac troponin C regulatory domain: a multi-scale simulation study. - Peter Michael Kekenes-Huskey (Public Library of Science (PLoS), 2012)
Troponin C (TnC) is implicated in the initiation of myocyte contraction via binding of cytosolic Ca²⁺ and subsequent recognition of the Troponin I switch peptide. Mutations of the cardiac TnC N-terminal regulatory domain have been shown to alter both calcium binding and myofilament force generation. We have performed molecular dynamics simulations of engineered TnC variants that increase or decrease Ca²⁺ sensitivity, in order to understand the structural basis of their impact on TnC function. We will use the distinction for mutants that are associated with increased Ca²⁺ affinity and for those mutants with reduced affinity. Our studies demonstrate that for GOF mutants V44Q and L48Q, the structure of the physiologically-active site II Ca²⁺ binding site in the Ca²⁺-free (apo) state closely resembled the Ca²⁺-bound (holo) state. In contrast, site II is very labile for LOF mutants E40A and V79Q in the apo form and bears little resemblance with the holo conformation. We hypothesize that these phenomena contribute to the increased association rate, k(on), for the GOF mutants relative to LOF. Furthermore, we observe significant positive and negative positional correlations between helices in the GOF holo mutants that are not found in the LOF mutants. We anticipate these correlations may contribute either directly to Ca²⁺ affinity or indirectly through TnI association. Our observations based on the structure and dynamics of mutant TnC provide rationale for binding trends observed in GOF and LOF mutants and will guide the development of inotropic drugs that target TnC.